Комп’ютерне моделювання деяких природних процесів для генерації ландшафтів - Станіславів, Олександр; Жолтовський, Олексій; Смалько, Олена (Kamianets-Podilskyi National Ivan Ohiienko University, 2024)
The article describes various approaches to the formation of relief structures with naturalistic shapes, which is useful for their further use in the gaming industry, in augmented reality environments, and for creating high-quality, believable visual content. Having studied a significant part of the mathematical tools for landscape formation, the authors distinguish among many physics-based methods the description of such natural processes as erosion, sedimentation, and creep of materials, which can be used to synthesize realistic terrain. Some methods for solving numerical hydroaeromechanics tasks with simplified conditions are effective for modeling various landscape features. For example, the Euler equation can be used to synthesize large terrain structures based on an incompressible inviscid fluid. Smaller landscape components can be shaped using shallow water equations. They can also be used to model erosion processes caused by the destruction of soil or rocks by a water flow. If you need to simulate riverbed erosion, you should use a semi-empirical family of stream power law equations. The Bateman-Burgers equation will also add natural shapes to the terrain, which will help to model various aspects of fluid motion, such as flow in rivers, seas, oceans, and wave phenomena. By neglecting the viscosity-related terms, assuming a fluid with a density similar to water, and thus simplifying the computational process, a comprehensive model can be augmented by applying the Hopf equation. It is only important to manage the balance between the desire for ideal landscape structures and the rational use of computing resources.